Aspects of modernization of micro enterprises sector by involving a new methods of management by creation of net structure - Janczewska, D. (Видавництво Львівської політехніки, 2014)
The article discusses issues concerning creation of a new method of management of micro enterprises as the answer to growing globalization processes and marginalization of small and micro enterprises in SMEs. The pressure of surrounding environment that affects the activities of SMEs is the main barrier for developing micro enterprises. They do not have enough potential and cannot compete with big enterprises and international enterprises. The present methods of management are created on the experience of big companies that realize the global market goals. It is very difficult to bring the methods and techniques of management applied in big organizations into micro enterprises having several employees. The article presents the possibilities of modernization of micro enterprises sector by creating micro enterprises net structures. The author’s own research conducted in 2000-2009 allowed to identify the effects from development of the new form of cooperation between micro enterprises in net structures. Розглянуто аспекти створення нового методу управління мікропідприємств як реакцію на процес зростання глобалізації та маргіналізації малих і мікропідприємств в МСП. Тиск навколишнього середовища негативно відображається на діяльності малих і середніх підприємств і є основною перешкодою для розвитку мікропідприємств. Вони мають неправильно структурований потенціал і неконкурентоспроможні на ринку з великими і міжнародними підприємствами. Актуальні методи управління базуються на досвіді великих компаній, які реалізовують глобальні ринкові цілі. Процес перенесення методів і прийомів управління, які використовувалися у великій організації, у практичні засоби мікропідприємств, із невеликою кількістю працівників, є дуже складним. У цьому дослідженні представлені можливості модернізації сектору мікропідприємств шляхом створення мережевої структури мікропідприємств. Власні дослідження, реалізовані у 2000–2009 рр., дали змогу визначити типи ефектів від розвитку нової форми співпраці між мікропідприємствами у межах мережевої структури.
Аспекти модернізації сектору мікропідприємств шляхом залучення нових методів управління через створення мережевої структури
Keywords: micro enterprises; globalization processes; methods of management; net structures; global market; мікропідприємства; мережеві структури; зростання глобалізації